Analisis Pengaruh Bauran Pemasaran, Loyalty Program, Intentions to Switch Terhadap Kepuasan Pelanggan dan Implikasinya Pada Loyalitas Pelanggan PT. Bank Negara Indonesia 46 Merauke - Lia Yudar Pratiwi (Jurnal Penelitian dan Pendidikan IPS, 2019)
This study aims to analyze the effect of marketing mix on customer loyalty, analyze the effect of loyalty programs on customer loyalty, analyze the effect of intentions to switch on customer loyalty, analyze the effect of customer satisfaction on customer loyalty, analyze the effect of marketing mix on customer loyalty through customer satisfaction and analyze the effect loyalty program to customer loyalty through customer satisfaction PT. Bank Negara Indonesia 46 Merauke. The sample in this study was 76 customers. The analysis technique uses path analysis. The marketing mix has a significant positive effect on customer loyalty. The loyalty program has a significant positive effect on customer loyalty. Intentions to switch has a significant negative effect on customer loyalty. Customer satisfaction has a significant positive effect on customer loyalty. The marketing mix does not have a significant effect on customer loyalty through customer satisfaction. Loyalty programs do not significantly influence customer loyalty through customer satisfaction. Intentions to switch affect customer loyalty through customer satisfaction PT. Bank Negara Indonesia 46 Merauke.